LOW-TEMPERATURE PHASE DECOMPOSITION IN METAL FROM IRON, STONY-IRON, AND STONY METEORITES - Yang C.W.; Williams D.B.; Goldstein J.I. (My University, 1997)
The microstructure of the outer taenite rim and cloudy zone of meteoritic metal was investigated using high resolution scanning electron microscopy and analytical electron microscopy. The microstructure is formed by a series of complex phase transformations at =<400°C. These transformations are interpreted using the Fe-Ni phase diagram.The outermost subzone (zone 1) of the outer taenite rim is composed of two single-phase layers, Ni3Fe and FeNi (tetrataenite). The Ni3Fe phase appears at the border between kamacite and the outer taenite rim. The inner two subzones (zones 2 and 3) in the outer taenite rim are two-phase with a matrix of tetrataenite and low Ni bcc precipitates. The three zone structure is a general feature in the outer taenite rim of metal particles in all major types of meteorites. The cloudy zone is composed of an island region and a bcc single phase honeycomb region containing #9.0 wt% Ni. The island region is a two-phase mixture of a L10 ordered fcc tetrataenite matrix and low-Ni bcc precipitates.The high-Ni taenite region, γ2, resulting from the monotectoid reaction, γ1 -> α + γ2, at 400°C remains as a supersaturated solid solution to lower temperatures and corresponds metallographically to the outer taenite rim. The width of the outer taenite rim varies inversely with the cooling rate of the meteorite. The γ', Ni3Fe, phase is formed when the high-Ni γ2 phase containing #53 wt% Ni undergoes an eutectoid reaction, γ2 -> α + γ' at about 345°C.The cloudy zone develops by spinodal decomposition below 350°C. Metastable γ2 island region of high Ni content and metastable γ1 honeycomb region of low Ni content are formed. The size of the constituents of the cloudy zone increases with increasing Ni content because the higher Ni regions enter the spinodal region at higher temperatures.The precipitates in the island region of the cloudy zone and in zones 2 and 3 of the outer taenite rim have essentially the same Ni content (14.2-14.7 wt%) and form at lower temperatures when the Ni content of γ2 is located in the γ1 + γ2 miscibility gap but outside the spinodal.If cooling rates or metamorphic reheating is to be studied at or below 400°C, the low temperature phase transformations must be considered. Improvement in simulation models will be difficult to make, however, because the diffusion rates in ordered FeNi, tetrataenite, and ordered Ni3Fe are not known.